Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Re visions, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Romance revisited - Pearce, Lynne; Stacey, Jackie (New York University Press, 1995)
Après des décennies de féminisme et de déconstruction, la romance reste fermement ancrée comme une préoccupation centrale dans la vie de la plupart des femmes. Les taux de divorce montent en flèche, la famille traditionnelle est remise en question de toutes parts et pourtant la romance semble indestructible. En termes de représentation culturelle, la popularité de la romance semble également incontestée. La fiction populaire, le cinéma hollywoodien, les feuilletons télévisés et les médias en général affichent tous un appétit apparemment sans limite pour les sujets romantiques. Les pièges de la romance classique – mariages blancs, chansons d’amour, Saint-Valentin – sont plus que jamais commercialement viables. Dans cette anthologie d'essais originaux, la romance est revisitée sous un large éventail de perspectives, non seulement dans la fiction et le cinéma, mais dans toute une gamme de phénomènes culturels. Les essais couvrent des sujets tels que la Saint-Valentin, les relations interraciales, les visions érotiques médiévales et la fiction romantique moderne, la relation entre la poétesse lesbienne HD et Bryher, la blancheur omniprésente du désir romantique, l'érotisme lesbien à l'ère du SIDA et la romance publique de Charles et Diane.
Keywords: anthologie; approches et analyses; arts; classisme; discipline; histoire et politique; outils; ouvrages de références; patriarcat; racisme; romance; sexisme; sexualité; systèmes d'oppressions; thématiques; études culturelles; études littéraires

The lesbian postmodern - Doan, Laura L. (Between men--between women, 1994)
Tous originaux de ce volume, ces essais évocateurs rédigés par des chercheureuses tels que Robyn Wiegman, Elizabeth Grosz et Judith Roof examinent un domaine encore intact de la critique littéraire et culturelle et de la théorie du genre, une postmodernité spécifiquement lesbienne. Les essais retracent, d’une part, comment certaines théories et productions culturelles lesbiennes mettent en avant une politique de différence et de marginalité et critiquent ainsi l’hégémonie patriarcale et hétérosexuelle. D’un autre côté, certains essais soulignent comment une esthétique postmoderne, avec sa valorisation de la différence, de la pluralité sexuelle et du flou des genres, contribue à la production culturelle lesbienne. Parmi les sujets abordés figurent les définitions changeantes des termes lesbien et postmoderne ; le potentiel et danger de ce nouveau territoire conceptuel dans la théorie, la représentation littéraire et visuelle et la culture populaire ; la lesbienne dans le cinéma hollywoodien ; les actrices Jodie Foster et Sandra Bernhard ; et des œuvres de Jeanette Winterson, Michelle Cliff et Gloria Anzaldua. Tout au long, les contributeurices abordent les questions et enjeux interdépendants de classe, de race, d’ethnicité, de postcolonialisme et de marchandisation.
Keywords: approches et analyses; arts; discipline; hétérosexisme; lesbianisme; patriarcat; personnes lesbiennes; postmodernisme; sexisme; système colonial; systèmes d'oppressions; études littéraires

L'écrivain - Brossard, Nicole (La nef des sorcières, 1992)
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cours; discipline; fem1000; pratiques féministes; premier cycle; périodes historiques; québec; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théâtre; écriture des femmes*; études littéraires

La nef des sorcières - Guilbeault, Luce; Blackburn, Marthe; Théoret, France; Gagnon, Odette; Blais, Marie-Claire; Pelletier, Pol; Brossard, Nicole; Guilbeault, Luce (L'Hexagone, 1992)
La création au Théâtre du Nouveau Monde de La nef des sorcières, pièce composée de sept textes d’auteures différentes, est reconnue comme un moment capital dans l’émergence du théâtre féministe militant au cours des années 1970 et 1980. En ce qui concerne la réception de ce spectacle et du texte publié, l’attention du public et de la critique se dirigeait surtout vers la thématique féministe véhiculée par la pièce et le commentaire qui s’y faisait sur le fonctionnement du patriarcat dans la vie privée des femmes. Cependant, l’objectif des auteures et des comédiennes dépassait largement le simple commentaire social. Ce n’était pas leur intention de réduire la scène théâtrale à une simple tribune politique. Luce Guilbeault, qui initia le projet et s’y engagea comme metteure en scène, auteure et comédienne, voulait avec les autres, en plus de susciter des discussions, ébranler les fondements sexistes du théâtre, élargir l’espace de l’imaginaire collectif, transformer la symbolique masculiniste de la culture québécoise, et élargir l’horizon d’attente de l’auditoire. Quand son Actrice en folie subit un trou de mémoire et enlève son costume dès son entrée en scène, c’est une ouverture remarquable au spectacle expérimental et à l’invention d’une nouvelle théâtralité au féminin qui se fait jour. C’est alors que commence la remise en cause radicale des pratiques, des codes, des règles et des conventions du jeu, des langages et de la forme canoniques du théâtre qui permettent depuis des millénaires l’esthétisation par le théâtre des idéologies et des fantasmes dominants sexistes.
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cours; discipline; fem1000; pratiques féministes; premier cycle; périodes historiques; québec; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théâtre; écriture des femmes*

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

L'interloquée ; Les oubliées de l'oubli ; [et] Dé/générée - Causse, Michèle (Trois, 1991)
« L’androlecte est en effet un soliloque. C’est la production mentale, disons la pathologie langagière, de l’Andros qui, victime d’une faille principielle, n’a pas su, pas pu, pas voulu accéder au chiffre deux et qui, s’étant érigé en seul locuteur, n’a pas eu d’autre interlocuteur que lui-même. Avant même de parler, une femme en "Androlecte est inter-loquée". Soit au sens propre "interdite-interrompue". Le dictionnaire – depôt sacré des mots de l’androlecte – ne donne-t-il pas comme exemple cette phrase, ô combien illuminante: "Faute d’interlocuteur, elle se parlait à elle-même". (Petit Robert, Léon Bloy). Bécassine ayant cru sans doute dans le langage comme communication. » p.15 éditions Trois, 1990
Keywords: approches et analyses; arts; discipline; hétérosexisme; lesbianisme; sexisme; systèmes d'oppressions; études littéraires

Surrealism and women - Caws, Mary Ann; Kuenzli, Rudolf E.; Raaberg, Gloria Gwen (MIT Press, 1991)
These sixteen illustrated essays present an important revision of surrealism by focusing on the works of women surrealists and their strategies to assert positions as creative subjects within a movement that regarded woman primarily as an object of masculine desire or fear.While the male surrealists attacked aspects of the bourgeois order, they reinforced the traditional patriarchal image of woman. Their emphasis on dreams, automatic writing, and the unconscious reveal some of the least inhibited masculine fantasies. The first resistance to the male surrealists' projection of the female figure arose in the writings and paintings of marginalized woman artists and writers associated with Surrealism. The essays in this collection explore the complexity of these women's works, which simultaneously employ and subvert the dominant discourse of male surrealists.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques